A multicenter retrospective review of antibiotic prescribing patterns for treatment of urinary tract infections in the primary care setting. Issue 6 (5th April 2021) - Mullakary, Jenny; Visintainer, Sarah; Tucci, Mitchell; Dionne, Brandon; Conley, Michael P.; Reid, Debra J.; Matta, Thomas M.; Bartucca, Macayla A.; Bouwmeester, Carla J.
Abstract: Introduction: It has been estimated that nearly 50% of antibiotics are inappropriately prescribed in the outpatient setting. Despite much discussion surrounding the importance of reducing these occurrences, the literature is limited in describing antibiotic prescribing patterns for urinary tract infections (UTIs) in the primary care setting. Objectives: The primary objective of this study was to evaluate if antibiotics for UTIs in primary care settings are prescribed concordantly with evidence‐based guidelines. Methods: This retrospective cohort study reviewed female patients 18 years and older treated in a primary care setting with a diagnosis of uncomplicated UTI. Treatment was analyzed for appropriateness of empiric antibiotic choice, duration of therapy, and dose. This information was then compared with treatment recommendations for UTIs per the 2010 Infectious Diseases Society of America (IDSA) guidelines. Antibiotic prescribing patterns were also analyzed in relation to the 2016 United States Food and Drug Administration (FDA) safety warning for fluoroquinolones. Results: A total of 388 UTI encounters over the 42‐month study period were included for analysis. Sulfamethoxazole/trimethoprim was the most frequently prescribed antibiotic (50.0%) followed by nitrofurantoin (26.3%) and fluoroquinolones (16.8%). A total of 71.6% of antibiotic agents selected for treatment of UTIs were not first line agents per the 2010 IDSA guidelines, which increased to 92.3% when considering dosing, duration, and renal adjustments. Culture and susceptibility results led to changes in empiric therapy, yet only 38.1% of the changes were considered guideline concordant. Linear regression comparing pre‐ and post‐FDA warnings indicated a 15% reduction in the proportion of fluoroquinolone prescriptions ( P < .001). Conclusion: A large disparity exists between antibiotic prescribing patterns and IDSA guideline recommendations. By identifying divergences from standards of practice, pharmacists can justify the need to integrate stewardship programs into primary care settings in order to optimize patient care.